(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Questions: Are the conditions Astrodaucus littoralis on the territory of the protected area is favorauble for this species? Locations: Regional landscape park “Tyligulsky” (Mykolayiv region). Methods: field studies of habitats of rare species Astrodaucus littoralis. Nomenclature: POWO (2025), Dubyna et al. (2019) Results: During the expeditions of 2023–2024, the distribution and habitat conditions of Astrodaucus littoralis were studied within the territory of the Tyligulsky Regional Landscape Park (Mykolaiv region). We found five local populations of A. littoralis, which are located on different spits of the estuary: Velyka Ukrainska, Mala Ukrainska and Anatolivska. The populations are quite distant from each other and somewhat coenotically and populationally different. Three local populations were studied on the Velyka Ukrainska Spit. In local population 1, the growth of 26 individuals of this species with well-developed ground shoots and inflorescences was recorded. The species grows on the area of the littoral wall of the Tyligulsky estuary with well-developed plant cover (total cover is 60 %). Local population 2 – A. littoralis was found in sparse grass stands, closer to the surf zone (total cover is 30 %). The presence of 10 developed individuals was recorded (of which: 4 – vegetative and 6 – generative). Local population 3 revealed in the surf zone, closer to the “tip” of the spit. Herb cover is almost absent (total cover is 10 %). 9 individuals were found in this locality (2 – vegetative and 7 – generative). Local popu-lation 4 was recorded on the Mala Ukrainska Spit. A. littoralis grows along the southern coast of the spit in the surf zone (total cover is 30 %). The presence of 11 individuals of A. littoralis on 25 m2 was noted. All plants were well-developed (9 – generative with fruits, 2 – generative with inflo-rescences). Local population 5 occurs on the Anatolivska Spit. We noted the presence of 13 individuals of A. littoralis in sparse plant cover (total cover is 30 %). All plants are well-developed (9 – generative, 4 – vegetative). Conclusions: A study of the current state of Astrodaucus littoralis habitats on the territory of the Tyligulsky Regional Landscape Park was conducted. Despite significant recreational pressure, the population of A. littoralis is characterized by a significant number of individuals of different ontogenetic stages with a predominance of mature generative ones, especially on the territory of the Mala Ukrainska Spit.